Novi Dan - Zaja, Tomislav (Croatia, 2013)
In many parts of the world people with intellectual or psychosocial disabilities who also have physical disabilities are sent to institutions in huge numbers, leaving them completely excluded from their communities. This happens for two main reasons: there is widespread societal prejudice against the disabled because of the way they look and their normal physical environments do not accommodate their disabilities. Instead of being confined to residential institutions that deprive them of any control over their lives, people with disabilities in Zagreb, Croatia can now live as independently as possible while receiving individualized support.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films